THE ANALYSIS OF LEARNING STRATEGY IN SPEAKING SKILL: A STUDY ON PEOPLE WITH DISABILITY - Muhammad Iqbal Adikusuma; Fakhri Fikri; Rasi Yugafiati (IKIP Siliwangi, 2018)
People with disability have their chance to get the education as well as the other people. While they continue their study on higher level of education, they learn several subjects, included English. One of the skills should be mastered in learning English is speaking. Their speaking skill may different with the ordinary people who can see how the lecturers produce the utterances and watch the movies, etc. Thus, the people with disability have their own learning stategy to achieve the speaking skills. They use those learning strategies because they hope to master the speaking skills as good as the ordinary ones no matter what. The research method is descriptive qualitative. There are two participants in the research. They use application of screen reader to drill the vocabulary and pronounciation. Screen reader is one of the applications that help people with disability to master speaking skill. It can be downloaded in playstore. They learn speaking skill autodidactly. They also brave to practice their speaking skill with lecturers and classmate of English Department. Keywords: people with disability, learning strategy, speaking skill